DISEÑO DE MATERIAL DIDÁCTICO BIDIMENSIONAL PARA LA ENSEÑANZA DE PRINCIPIOS MUSICALES A NIÑOS DE LA UNIDAD EDUCATIVA JOSÉ MARÍA ROMÁN - Padilla Saez, Henry David (2019)
Graphic design has a significant impact when communicate visually, and this, in turn, satisfies a need that can be resolved in a functionally and aesthetically for the user. For this reason, the research Project called “Design of two-dimensional didactic material for the teaching of musical principles to children of José María Roman Unit” is based on the knowledge of a designer, who is aware of the context of the research. The new way of learning and the ideal design proposals seek a link between graphic design and music, to offer a project of academic material that contributes to significant learning. The primary purpose of the research is to provide teaching resources to music education teachers, based on an analysis of teaching materials used in the classroom, where it was evident that there is no adequate material. Therefore the development of two educational musical was proposed: Do-Do the dominant musical play and musical Bingo. These games are elaborated based on the contents of the national curriculum of ECA (Cultural and Artistic Educational Department of Ministry of Education), concerning the garea of music also based on principles and elements of graphic design, which are essential for the development and sustenance of a proposal for educational games.